As contribuições da pesquisa-ação para a elaboração de políticas de formação continuada na perspectiva da inclusão escolar - Bento, Maria Jose Carvalho (2019)
This study’s aim is to analyze the contributions of critical-collaborative research-action in the construction of a continuous formation for education professionals, considering the inclusion of Special-Education target-public students in the Municipal Education System of Marataízes, ES, Brazil. This study is grounded on Jürgen Habermas’ Communicative Theory’s supposals as it seeks to sustain the methodological, epistemological and theoretical perspectives adopted. The critical-collaborative research-action is constituted after methodological and epistemological supposals, having the researcher-participant relationship as a principle for the production of knowledge through mutual understanding and sensitive hearing. It involves as its participants the research-group coordinator (Grufopees/CNPq-Ufes), two graduate students, one undergraduate student (with a scientific-initiation fellowship), and three Municipal Education Board officials from Marataízes. For data generation, strategies and instruments such as reflection-study groups, focal group, municipal files mapping, planning meetings and population statistical analysis are used, registering them in reports, voice-recording transcription, and field diaries. It indicates as result the necessity of assistance policies for Special-Education target-public with continuous formation for Education-System professionals. It evidences the research-action contributions in the processes experienced between researchers-academicians and researched-officials, mainly in the posture change from professionals, who became researchers, and in the composition of groups as a study-reflection dynamics, with elaboration of public policies. Furthermore, it signals the strength of critic-collaborative research-action in formative processes as another kind of knowledge-production rationality, no longer positivistic, but communicative, making thus possible the construction of continuous-formation policies under the inclusive schooling perspective by means of critical self-reflection.